Stink : the incredible shrinking kid - McDonald, Megan; Reynolds, Peter, 1961- (Cambridge, Mass. : Candlewick Press, 2005)
The shortest kid in the second grade, James Moody, also known as Stink, learns all about the shortest president of the United States, James Madison, when they celebrate Presidents' Day at school.
480
Accelerated Reader AR
Keywords: Size -- Juvenile fiction; Schools -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Presidents -- Juvenile fiction